The Relationship between Illness Acceptance, Cancer-Related Complaints and Psychological Distresses among Malaysian Cancer Patients - Ahmad, Mahadir; Chen, Yoke Yong; Ismail, Fuad Bin (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Aim: The present study investigated the relationship between psychological problems, illness acceptance and cancer-related complaints among Malaysian cancer patients. Methods: One hundred and six cancer patients were recruited and were requested to complete validated self-reported questionnaires that measured their psychological distresses, sleep quality, pain, fatigue and illness acceptance. Results: There was a significant relationship between cancer-related symptoms, illness acceptance and psychological distresses commonly experienced by local cancer patients (p < 0.05). Conclusion: Malaysian cancer patients with more cancer-related complaints reported a higher level of psychological distresses and poorer illness acceptance. Increased level of illness acceptance was suggested in managing cancer patients with psychological distresses and cancer-related complaints.